Contextualismo social na prática: a interpretação da teoria política de Bento Espinosa feita por Ellen Meiksins Wood - Cardoso, Juliane Cristina Helanski (2017)
The return to democratic theory of Benedict Espinosa by the Marxists Antonio Negri and Marilena Chauí has raised many controversies. Ellen Meiksins Wood, who is also a Marxist, strongly disagrees with the conclusions that Negri and Chauí arrived at by stating that Spinoza's democratic theory is revolutionary and emancipatory. Ellen Wood believes that Spinoza's democratic theory was, in fact, an oligarchic republican theory that in practice corresponded to the political and social interests of the Dutch trading elites. How can we explain such divergent and even contradictory interpretations by intellectuals of the same political orientation (all of them admittedly Marxist)? What is more curious is that Ellen Wood's conclusions are closer to the neoconservative Leo Strauss's reading of Spinoza, by methodological means and with a very different political bias, which led him to conclude that Bento Espinosa's democratic theory is about A liberal democracy of religious origin. We believe that the answer can be search in the analysis of how each of them considered the relationship between political ideas and the social context. In this sense, the main objective of this paper is to discuss the methodological assumptions of Neal Wood's social contextualism based on the "renewal" of Marxian historical materialism and the application made by Ellen Wood in the interpretation of Bento Espinosa's political theory.